People and Nature in the Development of Border Tourism in Indonesia - RACHMAWATI, Iva; DEWI, Machya Astuti; SUGIARTO, Meilan; ISSUNDARI, Sri (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019, 2020)
This paper aims to explain the importance of community support in the development of border tourism in Indonesia. Indonesia's border areas are generally lagging regions with very minimal public facilities. The paradigm shift in the border management area from security to prosperity puts the border area into a front-page. Border tourism then becomes one of the choices to encourage the progress of the border area. This study was conducted in 3 Indonesian border areas: Indonesia-Malaysia border, Indonesia-Papua New Guinea border, and Indonesia-Timor Leste border. Field observations and interviews have been conducted with residents in the border area and local government. Secondary sources such as publications and scientific journals are also used as research data. The result indicated that inter-community interaction between neighboring countries plays an important role in developing border tourism in Indonesia. Their involvement in the border festival and the trade transaction activities succeeded in increasing the popularity and number of visitors to the border. This proves that the key to the success of tourism development at the border is not solely due to infrastructure development or government support. The lack of access and facilities at the border can be overcome by maximizing community activities, including the participation in border festivals and ecotourism.